JOB CHARACTERISTIC AND WORK FAMILY CONFLICT EFFECTS ON EMPLOYEE OCCUPATIONAL STRESS AT TVRI NORTH SULAWESI - Roringpandey, Prisky Mercedes; Pangemanan, Sifrid S.; Pandowo, Merinda . (Universitas Sam Ratulangi, 2017)
Abstract: Over the past few decades, almost three billion employees globally are faced with a serious problem in every company called â€œstressâ€ which affects employeeâ€™s performance and it has become an essential part of every field work. This study aims to determine Job Characteristic and Work Family Conflict Effects on Employee Occupational Stress. The number of sample is 55 respondents. The research was conducted in TVRI Sulut in Tikala Ares Hill of Manado City. Data analysis using multiple linear regression analysis, t test and F test. The results showed that, based on the results of hypothesis testing in particular the model of the research found that the research model consisting of : job characteristic, and work family conflict has a positive and significant influence on employee occupational stress. Job characteristic become the most highest impact variable on employee occupational stress in this research. Work family conflict become the second highest impact variable on employee occupational stress in this research. Suggestions of this research: management in TVRI North Sulawesi should make this research finding become human resource strategy of the corporation. The management must focused the strategy to manage employee occupational stress by pay attention to job characteristic and work family conflict.Â Keywords: job characteristic, work family conflict, employee occupational stress